Effect of Weeding on Production of Eulaliopsis binata in Shiwalik Hill Forest - Pacholi, R. K.; Bankhwal, D. P. (Indian Forester, 1999)
This paper contains observations on effect of weeding on Bhabar grass (Eulaliopsis binata) growing in Shiwalik hill forests naturally. Maximum yield was obtained in three times weeded areas during the growth period (10.6 qtl/ha). The grass yield was found significantly different in weeded and unweeded areas reflecting beneficial effect of weeding in yield of economic grass E. binata.